THE PROBLEMS OF ECONOMIC TERMINOLOGY AND ITS IMPACT ON TRANSLATION - Mansurova Nodira Anvaronva (Western European Studies, 2025)
The modern linguistic studies confirm that keeping pace with modern linguistic norms requires careful usage of terminology in order to be properly employed through which the translation process is promoted and the problem of translating the specialized terminology in general and particularly economic terms are among the problematic encountered in transferring knowledge from foreign languages to Uzbek language. The purpose of this study is to analyze these problems in order to propose solutions for the unification of the term in English, refuting the reasons for the unification of the English terminology, because the terms are the keys to science, so if there are multiple terms equivalent to a single one, this leads to a disturbance in understanding and reflects negatively on the assimilation of knowledge, and contributes to the confusion of the entire translation process.
Keywords: Terminology; economic terminology; specialized language